The potential of remote XR experimentation: Defining benefits and limitations through expert survey and case study - Ratcliffe, Jack; Tokarchuk, Laurissa (Frontiers in Computer Science, 2022)
Experimentation using extended reality (XR) technology is predominantly conducted in-lab with a co-present researcher. Remote XR experiments, without co-present researchers, have been less common, despite the success of remote approaches for non-XR investigations. In order to understand why remote XR experiments are atypical, this article outlines the perceived limitations, as well as potential benefits, of conducting remote XR experiments, through a thematic analysis of responses to a 30-item survey of 46 XR researchers. These are synthesised into five core research questions for the XR community, and concern types of participant, recruitment processes, potential impacts of remote setup and settings, the data-capture affordances of XR hardware and how remote XR experiment development can be optimised to reduce demands on the researcher. It then explores these questions by running two experiments in a fully "encapsulated" remote XR case study, in which the recruitment and experiment processes is distributed and conducted unsupervised. It discusses the design, experiment and results from this case study in the context of these core questions.